PENGARUH SUKU BUNGA, INFLASI, DAN NILAI TUKAR RUPIAH TERHADAP INDEKS LQ45 DI BURSA EFEK INDONESIA PERIODE 2007-2021 - Octovian, Reza; Mulidia, Mutiara (Journal of Research and Publication Innovation, 2023)
This study aims to examine the effect of interest rates, inflation, and the rupiah exchange rate on the LQ45 Index on the Indonesia Stock Exchange for the period 2007-2021. The research methodology used is quantitative descriptive method. Data collection takes data related to related macro economics (Interest Rates, Inflation, Rupiah Exchange Rates, and LQ45 Index) from online data searches, namely through BI.go.id, Bps.go.id, www.idx.co.id, and finance.yahoo.com. The results of this study indicate that the variabels partially Interest Rates have no effect and are not significant, Inflation has no effect and is not significant, and the Rupiah Exchange Rate has an effect and is significant on the LQ45 Index. While simultaneously Interest Rates, Inflation, and the Rupiah Exchange Rate have a significant effect on the LQ45 Index.